1992
DOI: 10.1126/science.1455235
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Arginine-Evoked Insulin Secretion

Abstract: 0.3% Triton X-1 00, at 370C for 1 hour. They were then rinsed in buffer, air-dried, and coverslipped. Scale bar, 100 g±m. 1376an earlier study that used rat islets, no difference in nitrite production was seen after treatment with L-arginine (1 mM) or NG-nitroarginine methyl ester (NAME) (1 mM) without arginine (3). Islets accumulate and convert exogenous L-arginine primarily into L-omithine and urea, not into citrulline, the expected product of a NO synthase (4). Also, the response to L-arginine described by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 9 publications
0
18
2
Order By: Relevance
“…Very recently, evidence has been obtained direct depolarizing effect of the cationic amino acid. Since for the occurrence of NO synthase activity in both endocrine NO synthase inhibition increased L-arginine-induced insulin cells and nerves of the islets of Langerhans (Schmidt et al, release (Panagiotidis et al, 1992) we suggested that the 1992; Vincent, 1992;Panagiotidis et al, 1992;Corbett et al, stimulating effect of L-arginine was in part counteracted by 1993). Previous data (Laychock et al, 1991;Schmidt et al, the concomitant production of NO.…”
Section: Introductionmentioning
confidence: 86%
“…Very recently, evidence has been obtained direct depolarizing effect of the cationic amino acid. Since for the occurrence of NO synthase activity in both endocrine NO synthase inhibition increased L-arginine-induced insulin cells and nerves of the islets of Langerhans (Schmidt et al, release (Panagiotidis et al, 1992) we suggested that the 1992; Vincent, 1992;Panagiotidis et al, 1992;Corbett et al, stimulating effect of L-arginine was in part counteracted by 1993). Previous data (Laychock et al, 1991;Schmidt et al, the concomitant production of NO.…”
Section: Introductionmentioning
confidence: 86%
“…Some investigators described NOS-immunoreactivity and/or NADPH-diaphorase staining in the majority of rat and mouse islet cells [6,12], whereas others failed to detect NOS-immunoreactivity in human and rat islets [13±15]. Apart from the important influence of the fixation procedures used [14,15] and species differences, the existence of local isoforms of NOS may account for the observed discrepancies [15].…”
Section: Discussionmentioning
confidence: 99%
“…Thus L-arginine-derived NO has been suggested not to be involved in L-arginine stimulation of insulin secretion (6,14,15), to enhance L-arginine stimulation of insulin secretion (16,17), or to inhibit Larginine stimulation of insulin secretion from pancreatic b-cells (18)(19)(20). In accordance with a possible significance of NO in L-arginine stimulation of insulin secretion, islets have been found to express the constitutive, Ca 2+ /calmodulin-dependent nitric oxide synthase (cNOS), which may exhibit glucose-sensitive NO synthesis in the presence of L-arginine (16,20).…”
Section: Introductionmentioning
confidence: 99%